2009
DOI: 10.1016/j.biomaterials.2009.07.032
|View full text |Cite
|
Sign up to set email alerts
|

The effect of osteoprotegerin gene modification on wear debris-induced osteolysis in a murine model of knee prosthesis failure

Abstract: Using an in vivo adeno-associated virus (AAV)-mediated gene transfer technique, this study evaluated the therapeutic effects of an Osteoprotegerin (OPG) transgene against orthopaedic wear debris-induced osteolysis in a long-term murine model. A titanium pin was surgically implanted into proximal tibia of Balb/c mice to mimic a weight-bearing knee arthroplasty, followed by an intraarticular challenge with Ti-particles to provoke periprosthetic inflammation and osteolysis. rAAVhOPG or AAV-LacZ vectors were injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 32 publications
(46 reference statements)
3
42
0
Order By: Relevance
“…As other studies indicate, we also confirmed that Ti particles induced an obvious inflammatory reaction and increased the expression of pro-inflammatory cytokines [7,9,11,13]. These cytokines, particularly TNF-a, IL-1b and IL-6, promote the activation of osteoclasts and eventually contribute to the osteolytic process.…”
Section: Discussionsupporting
confidence: 90%
“…As other studies indicate, we also confirmed that Ti particles induced an obvious inflammatory reaction and increased the expression of pro-inflammatory cytokines [7,9,11,13]. These cytokines, particularly TNF-a, IL-1b and IL-6, promote the activation of osteoclasts and eventually contribute to the osteolytic process.…”
Section: Discussionsupporting
confidence: 90%
“…However, this can be judged as a preliminary study, as no bone loss has been quantitatively proved (polystyrene particles used), only a few animals were included, the exact number of particles delivered could only be grossly extrapolated, and-surprisingly-no particles were observed on any histological bone section. We consider that major improvements were provided by Yang et al [48] and Zhang et al [49]. These authors used an effective long-term implant (pin implanted into proximal tibia to form a contiguous surface with the articular cartilage); an implant that stays well fixed after six months without particle challenge; monthly intra-articular injections for six months to achieve a long-term course (chronic reaction); pull-out tests as additional outcome measure; and most of all, in vivo gene transfer (using adenoassociated virus) to improve the delivery system of OPG-related therapy.…”
Section: Respective Discussionmentioning
confidence: 99%
“…The parameters were 45 mm isotropic voxel size, 400 projections, 400 ms exposure time, 80 kW voltages, and 450 mA current as described previously. 22 The micro-CT scans were performed again after euthanasia. Following acquisition and reconstruction, image data were analyzed using GEHC MicroView 1 software to calculate the bone mineral densities (BMD) changes on the implanted bone chips.…”
Section: Micro-computerized Tomography Assessmentmentioning
confidence: 99%
“…22,23 The presence of dark purple staining granules in the cytoplasm was used to identify TRAP positive cells.…”
Section: Histological Evaluation and Image Analysismentioning
confidence: 99%